LEGAL REASONING COMPARATIVE MODEL OF ASY SYATIBI AND GUSTAV RADBRUCH - Isman, Isman (Nurani, 2020)
This paper discusses the comparative legal reasoning of Asy Syatibi and Gustav Radbruch in their philosophical basis framework. By using a comparative analysis of reasoning models, both examine the influence between philosophical modalities and legal reasoning models developed by both legal theorists. The results of the research show that the ontological stance of Asy Syatibi is identical to transcendental-based foundationalism, while Gustav Radbruch positions himself on transcendental idealism. Meanwhile, the identification of epistemological modalities Asy Syatibi is more inclined to internal coherence, while Gustav Radbruch is influenced by the flow of methodical dualism and empirical realism. As for his axiological modality, Asy Syatibi is much influenced by maqashid ethics as a legal goal, while Gustav Radbruch is influenced by deontic ethics. Keywords: substantive induction, maqashid ethics, coherentism, methodical dualism, deontic ethics.